A Study on the Effects of Reputation-based Decision on the Dynamics of Public Goods Game with Punishment, Signaling and Gossiping Mechanisms - Mendoza, Mariana R.; Bazzan, Ana L. C. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2011: Anais do VIII Encontro Nacional de Inteligência Artificial, 2011)
In public goods game individuals contribute in favor of a common benefit. However this attracts free-riders, who profit the benefits generated by the group regardless their contribution decision. Although one would expect a cooperation collapse within a rational society, what is observed, in fact, is the emergence of cooperation. In the present work we not only address mechanisms such as punishment, signaling, and gossiping, but also add reputation-based decision-making to the process. We show that the dynamics of public goods game changes with the inclusion of the latter mechanism. Specifically, a decrease in the average wealth and contribution is observed because agents tend to be more selective. This holds a similarity with real-world situations: Human beings do act based on reputation about their partners.